Pengajaran Guru terhadap Keterampilan Emosial ABK di Bunga Bangsa Universal School melalui Dukungan Orang Tua - Arlin Arviana; Mulya Virgonita I Winta; Shinta Pratiwi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Children with Special Needs (ABK) often encounter challenges in emotional skills, including recognizing, managing, and appropriately expressing their emotions. However, these aspects are frequently overlooked in the learning process within inclusive school settings. In fact, appropriate teacher intervention and consistent parental support can significantly enhance the emotional capabilities of ABK. This study aims to examine the teaching strategies employed by educators in fostering the emotional skills of Children with Special Needs at Bunga Bangsa Universal School, while also considering the involvement of parental support. A quantitative approach was adopted, utilizing a case study method. The research involved 10 teachers and 50 parents of ABK, selected through a saturated sampling technique. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, processed via SmartPLS version 3.0 software. The findings indicate that both the teaching strategies implemented by teachers and parental support have a positive and significant impact on the emotional development of ABK. Moreover, parental support serves as an effective mediator in reinforcing this relationship. Based on these results, it is recommended that educators adopt responsive and collaborative teaching approaches, and maintain intensive communication with parents. Schools are also encouraged to provide specialized training for both teachers and parents to enhance their understanding of the emotional needs of children with special needs.